The relation between functional magnetic resonance imaging activations and single-cell selectivity in the macaque intraparietal sulcus - Van Dromme, Ilse C.L.; Vanduffel, Wim; Janssen, Peter (NeuroImage (Orlando, Fla.), 2015)
Previous functional magnetic resonance (fMRI) studies in humans and monkeys have demonstrated that the anterior intraparietal sulcus (IPS) is sensitive to the depth structure defined by binocular disparity. However, in the macaque monkey, a single large activation was measured in the anterior lateral bank of the IPS, whereas in human subjects two separate regions were sensitive to depth structure from disparity. We performed fMRI and single-cell experiments in the same animals, in a large number of recording sites in the lateral bank of the IPS. The fMRI interaction effect between the factors curvature (curved or flat) and disparity (stereo or control) correctly predicted the location of higher-order disparity selective neurons that encoded the depth structure of objects. However the large region in the IPS activated by depth structure consisted of two patches of higher-order disparity-selective neurons, one in the anterior IPS and one located more posteriorly, surrounded by regions lacking such selectivity. Thus the IPS region activated by curved surfaces consists of at least two patches of higher-order disparity selective neurons, which may reconcile previous fMRI studies in monkeys and humans.